(untitled) (Journal of Accessibility and Design for All, 2020)
Air travel is very restricted for individuals with mobility limitations and there is a need for the design of improved accommodation for individuals in wheelchairs on an aircraft. The aim of this paper is to present an aircraft wheelchair design, referred to as the Aircraft Combination Wheelchair Seat (ACWS), that meets the requirements of the dimensions of the Airbus A321 aircraft aisles and facilitates aircraft mobility. This study focuses on the process of the design and the analysis undertaken. The universal design approach ensures the product can be used for more than one function, including, the ability to be fully integrated into the airline seat or the reverse, to be detached from the seat frame. Finite element analysis performed on both options concluded that the product was technically feasible.